Correlations Among Classroom Emotional Climate, Social Self-Efficacy, and Psychological Health of University Students in Taiwan. Issue 4 (May 2021) - Hong, Fu-Yuan; Chiu, Shao-I; Huang, Der-Hsiang; Chiu, Su-Lin
The purposes of this study were to explore the correlations among classroom emotional climate, student social self-efficacy, and student psychological health. This study treated 392 university students as the research participants. The results of the confirmatory factor analysis showed that the factor structure of classroom emotional climate and social self-efficacy had a good fit. The results showed that classroom emotional climate could significantly affect social self-efficacy, that social self-efficacy could significantly predict self-esteem and depression, and that self-esteem could also significantly predict depression. Finally, the research results were discussed, and relevant suggestions were proposed for schools, teachers, and future research.